209k views
4 votes
Factor the expression completely.

4n2 + 28n +49
. (2n + 7) (2n +7)
(2n + 7) (2n - 7)
(2n – 7)
4n (n + 7) + 49
NEXT QUESTION
ASK FOR HELP

User Isuruf
by
6.4k points

1 Answer

4 votes

Answer:

(2n + 7) (2n +7)

Explanation:

To solve this problem we need to factorize 4n^2 + 28n +49 as shown below


4n^2 + 28n +49\\=>4n^2 + 14n + 14n +49\\=>2n(2n + 7) + 7(2n +7)\\=> (2n + 7) (2n +7)

thus, after factorization we see that first option is correct one

(2n + 7) (2n +7)

we can validate this by expanding it

2n (2n +7) + 7 (2n+7)\

=> 4n^2 + 14n + 14n + 49 = 4n^2 + 28n +49 (which is equal to the problem stated expression)

User Torinthiel
by
6.5k points